2007
DOI: 10.1016/j.brainres.2007.07.033
|View full text |Cite
|
Sign up to set email alerts
|

The neural substrates of enhanced salt appetite after repeated sodium depletions

Abstract: Sodium appetite is associated with a form of behavioral plasticity in which animals experimentally depleted of sodium progressively increase their intake of hypertonic NaCl over several successive (on 2 to 4 occasions) depletion. The present experiment explored the nature of this plasticity by quantifying Fos-immunoreactivity (Fos-ir) in structures implicated in the mediation of sodium appetite and in the signaling of reward. Rats were depleted of sodium with the diuretic furosemide three times (3F), one time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 26 publications
4
57
0
Order By: Relevance
“…There appears to be a significant overlap in the neural substrates involved in drug addiction and sodium appetite sensitization, and cross-sensitization has been demonstrated between sodium depletion and psychostimulant treatment [26,196]. Rats depleted of sodium multiple times show a neurochemical profile similar to that seen following sensitization to drugs of abuse [17,26] and demonstrate a craving for sodium as exhibited by an increased breakpoint in a progressive fixed ratio operant task [14]. These findings suggest that changes in sodium status can alter the chemistry and anatomy of putative reward pathways in the brain, the same pathways impacted by drugs of abuse and potentially involved in maintaining addiction.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…There appears to be a significant overlap in the neural substrates involved in drug addiction and sodium appetite sensitization, and cross-sensitization has been demonstrated between sodium depletion and psychostimulant treatment [26,196]. Rats depleted of sodium multiple times show a neurochemical profile similar to that seen following sensitization to drugs of abuse [17,26] and demonstrate a craving for sodium as exhibited by an increased breakpoint in a progressive fixed ratio operant task [14]. These findings suggest that changes in sodium status can alter the chemistry and anatomy of putative reward pathways in the brain, the same pathways impacted by drugs of abuse and potentially involved in maintaining addiction.…”
Section: Discussionmentioning
confidence: 84%
“…A recent experiment in our laboratory has elaborated on the potential neural mechanisms involved in facilitating sodium appetite sensitization [17]. We have found that experience with multiple sodium depletions differentially changes neural activity as a function of experiencing repeated deficits.…”
Section: Neural Substrates and The Mediation Of The Rewarding Aspectsmentioning
confidence: 99%
See 3 more Smart Citations